Exhalation of 1-131 after radioiodine therapy: time dependence and chemical form - Schomäcker, K.; Fischer, T.; Eschner, W.; Gaidouk, M.I.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: The change of both amount and chemical forms of radioiodine exhaled in the air of rooms with patients on the therapy ward should be investigated depending on radioactivity applied, time after application, and kind of thyroid disease. Methods: The air of ward-rooms of 62 patients with thyroid carcinoma, Graves’ Disease, and autonomy which received different therapy doses, was investigated with an portable constant air flow sampler. Different chemical iodine species (organic, elemental, aerosol bound) were collected during 8 hr in various filters until 3 days after application of the radioiodine capsule, according to their chemical form. The radioactivity in the filters was measured with a well counter on defined time points after application. Results: The radioactivity exhaled was between 0,008 and 0,03% related to activity of radioiodine applied. The percentage of radioiodine exhaled related to the activity applied, differed significantly depending on disease and changed as follows: Grave’s Disease > autonomy > carcinoma. The exhalation of radioiodine became stronger with increasing applied activities and showed an exponential decrease with time. The most part of radioiodine was present in organic bound form. This organic portion decreased with time in favour of the other iodine species. Conclusion: The degree of accumulation of radioiodine orally applied within thyroid seems to be in direct proportion to the extend of its exhalation. Further measurements directly in the breathing air of RIT-patients are necessary, in order to clarify the relationship between degree of thyroid uptake and quantity as well as chemical form of radioiodine exhaled.
Keywords: Radioiodine; exhalation; therapy; thyroid